1998
DOI: 10.1002/j.1552-4604.1998.tb04468.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gender on Adrenergic Receptor Responsiveness

Abstract: This study was conducted to determine whether gender differences exist in adrenergic receptor sensitivity and baroreflex response. Adrenergic receptor sensitivity was assessed by administering sequentially increasing intravenous doses of phenylephrine and isoproterenol. Baroreflex sensitivity was determined from the slope of pulse intervals plotted against phenylephrine-induced rise in systolic blood pressure (SBP). Drug-induced changes in heart rate, blood pressure, and brachial artery diameter were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
5
24
1
1
Order By: Relevance
“…Moreover, women often demonstrate less effective BP regulation than men during acute challenges (eg, orthostatic stress) and in response to vasoactive drugs. 1,2,4,6,[11][12][13][14] The responsible mechanisms have not been identified, but the results of the present study indicate that a reduced ability for BRB of acute changes in BP may play a central role in the less effective short-term BP control observed in women.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Moreover, women often demonstrate less effective BP regulation than men during acute challenges (eg, orthostatic stress) and in response to vasoactive drugs. 1,2,4,6,[11][12][13][14] The responsible mechanisms have not been identified, but the results of the present study indicate that a reduced ability for BRB of acute changes in BP may play a central role in the less effective short-term BP control observed in women.…”
Section: Discussionmentioning
confidence: 63%
“…The present results represent the first direct measurements of systemic ␣-adrenergic vascular responsiveness in men and women and correct previous findings of gender-related differences in responsiveness based on BP responses to systemic infusions of ␣-adrenergic agonists with intact baroreflexes. 13 We have shown that circulating levels of vasopressin increase in response to the decrease in BP produced by GB. 7,15,19 The vasoconstrictor effects of vasopressin can counteract the reductions in BP during GB and thus lead to an underestimation of tonic ANS support of BP.…”
Section: Tonic Ans Support Of Bpmentioning
confidence: 89%
See 2 more Smart Citations
“…Again, these results are in accordance with previous studies. 8,9 These functional experiments also demonstrate that the vascular response caused by elevated luminal concentrations of noradrenaline is different from that released neuronally. 10 An increase in systemic plasma concentrations of noradrenaline by exogenous infusion by approximately nine-fold as compared to tyramine did only translate into a three-fold increased blood pressure response.…”
mentioning
confidence: 74%